LCD graphic monitoring for energy saving control application - Norazianti, Kaharudin (2008)
This project is describe about the designing of control system in order to diminish energy wasting occur at the lecture halls. The main reason of the energy wasting is because of the position of lighting and air conditioning systems’ switches are located separately and at different places in the lecture hall, thereby make it difficult to lecturers and students to find the switch in order to on and off the equipments. In addition, it was make complicated and wasting time for students and lecturers to find the correct switch to on and off the equipment because switches are not denoted for which one lighting system and air conditioning system. This project can be divided into two major parts. The first one is an energy saving control system part, which consists of Graphic Liquid Crystal Display monitoring system and switching module whereas the second part is circuit driver of lighting and air conditioning development. LCD Graphic and switching module are used as a user interface where user merely needs to push buttons, which placing on the user interface plate in order to switch on or off the lighting and air conditioning system. The software programming of the PIC acts as the brain of LCD Graphic Monitoring for energy saving control system to control overall of the project performances.